The Influence of the Principal’s Leadership Style and Physical Work Environment on Teacher’s Performance - Kushendratno, Kushendratno; Arafat, Yasir; Furkan, Nuril (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to determine and analyze (1) the influence of the principal’s leadership style on teacher’s performance; (2) the influence of the work environment on teacher’s performance; and (3) the influence of leadership style and work environment partially or jointly on teacher’s performance. This research is a quantitative research with partial correlation method. This research was conducted at SMK Negeri Ilir Barat I Palembang with 126 teachers as respondents. Data collection techniques using questionnaires and documentation. Validity test uses construction validity and content validity. While the reliability test uses Cronbachh’s Alpha. The analysis prerequisite test used the normality test, linearity test, heteroscedasticity test, and multilinearity test, and the data were analyzed using simple regression and multiple regression techniques. The results showed that: (1) there was a positive and significant effect of the principal’s leadership style on the performance of State Vocational High School teachers in Ilir Barat I Palembang with a presentation of 22%; (2) There is a positive and significant effect of the work environment on the performance of State Vocational High School teachers in Ilir Barat I District, Palembang with a presentation of 19.4%; and (3) there is a positive and significant influence of the principal’s leadership style with the work environment on teacher’s performance. State Vocational High School in Ilir Barat I District, Palembang with a presentation of 21.8% while 78.2% was determined by other factors not included in this study.